Adsorption Of Terramycin On Activated Carbon Using Response Surface Methodology (RSM) - Husaini, Noor Syaza (Universiti Sains Malaysia, 2017)
The adsorption of terramycin onto wood-based activated carbon (WAC) is investigated in a batch adsorption process. Removal efficiency of terramycin onto non-modified WAC is compared with the modified WAC. Modified WAC is prepared by impregnation method using five types of solution which are HCl, H2SO4, HNO3, Cu(NO3)2, and KOH. The maximum adsorption capacity of terramycin on WAC impregnated with 1 wt % of Cu(NO3)2 is obtained with 99.85% removal efficiency. The adsorption is optimized by using response surface methodology (RSM) considering various parameters including pH value (3-7), initial concentration (5-25mg/L) and temperature (30-50 ⁰C). Three sets of optimum conditions are found to be optimum for terramycin adsorption on non-modified and modified WAC based on the Central Composite Design (CCD) using RSM (pH 7, 25 ppm, 50 ⁰C; pH 7, 5 ppm, 50 ⁰C; pH 3, 5 ppm, 50 ⁰C) (pH 7, 20 ppm, 36.4 ⁰C; pH 6.5, 20 ppm, 42.3 ⁰C; pH 6, 23 ppm, 39.3 ⁰C), respectively. One linear and one quadratic polynomial equations are developed to predict the percentage of removal efficiency. The experimental results indicated reasonable agreement with the predicted values. Based on ANOVA statistical value, the adsorption of terramycin onto WAC has been found to be highly significant, with low probability (p) values (<0.05). The maximum experimental terramycin removal efficiencies with the least error percentage of 93.85% and 99.63% for non-modified and modified WAC, respectively are obtained based on the validation model of optimum conditions.